Mortality of downstream migrating European eel at power stations can be low when turbine mortality is eliminated by protection measures and safe bypass routes are available. Issue 3 (24th July 2019) - Økland, Finn; Havn, Torgeir B.; Thorstad, Eva B.; Heermann, Lisa; Sæther, Stein Are; Tambets, Meelis; Teichert, Maxim A. K.; Borcherding, Jost
Abstract: The abundance of the European eel has seriously declined during recent decades. Hydropower production is one of the main threats, and solutions at power stations are needed to reduce the mortality of the downstream migrating silver eel. We examined the mortality, migration routes, and behavior of silver eel at a power station in Germany, after the power station was rebuilt to reduce the mortality of downstream migrating fish. Of 270 eels implanted with radio transmitters and released upstream of the power station, 222 eels passed the power station, primarily in October and November, although some descended during winter and spring. Most eels followed the main flow and passed over the spillway gate (59% and 49% in the 2 study years) or followed the route toward the bar racks in front of the turbines (24% and 27%), where they were guided to a route outside the turbines via the flushing channel. Some eels used the vertical slot fish passage (12% and 8%), whereas few used a nature‐like fishway, canoe pass, or custom‐made bypasses for eel. The eels showed large individual variation in migration timing, migration speeds, and choice of bypass. No eels were killed in the turbines, as none passed through them, likely due to the narrow bar spacing of the racks (10 mm). The results demonstrated that the mortality of eel passing power stations can be low (0–4% and 0–8% in the 2 study years) when the turbine intake is covered by racks hindering eels from entering turbines and safe bypass routes are available. Mortality estimates are given as ranges because the fate of 4% and 8% of the individuals could not be determined. Potential mortality could have been related to injuries in the bypass routes or increased predation risk, but there were no indications of injuries caused by installations in any of the bypass routes.